Politici de ocupare a forţei de muncă: Studiu de caz – judeţul Mureş - Georgescu, Maria-Ana (Calitatea Vieții, 2006)
The concept of life quality is difficult to be rendered an exact shape, yet it can be revealed by a series of indicators and one of them, which is also our choice, is employment. This study analyses this very complex issue of work placement. Within a market economy, where work demand and offer are defined by wage conditions, full employment cannot be made. Non-employment is a concept that includes both the unemployed and the persons who don’t want or cannot perform a waged activity. The analysis of unemployment, of its boundaries, of the policies for its prevention, has been performed within the context of social policies, more exactly of placement policies. The stress on employment active policies and on their actual fulfillment are exemplified for Mures County, the result being a comparative analysis of statistics data from the national level and from the Work Placement County Agency, at the end of the first semester of 2005. The county economic situation and the active measures taken by Work Placement County Agency resulted into a lower share of unemployment by 1.6% with respect to the national unemployment share, in June, 2005. To conclude, we should mention the thing that, on one hand the measures for work placement which are currently supported by public funds in Romania would use, as an alternative, a larger private initiative and, on the other hand this area can become a favorable background for an active involvement of the specialists, including those from universities, with the purpose of supporting the local communities, both from the offer and the demand sector of work market, just for improving employment indicators.